2013
DOI: 10.1902/jop.2012.110675
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrushing Education via a Smart Software Visualization System

Abstract: Background: The aim of this study is to evaluate the efficiency of a recently developed smart digital toothbrush monitoring and training system (DTS) in terms of correct brushing motion and grip axis orientation in an at‐home environment.Methods: Twenty‐one participants (11 test individuals [DTSG] and 10 control individuals [COG]) received instructions on the modified Bass technique (MBT) after their toothbrushing performance was monitored and they received professional tooth cleaning (T0). After 36 hours (T1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
2
35
0
4
Order By: Relevance
“…[14], Braun's SmartGuide was used to study the effects of real-time feedback on the quality of toothbrushing, in which they found a significant improvement in brushing habits when using this system. Other research has been conducted on the analysis of toothbrushing behavior using optical motion capture systems [2], [13] and embedded accelerometer sensors [11], [15], [16], [17], [25]. In particular, a system developed in Ref.…”
Section: Sensing Toothbrushingmentioning
confidence: 99%
See 2 more Smart Citations
“…[14], Braun's SmartGuide was used to study the effects of real-time feedback on the quality of toothbrushing, in which they found a significant improvement in brushing habits when using this system. Other research has been conducted on the analysis of toothbrushing behavior using optical motion capture systems [2], [13] and embedded accelerometer sensors [11], [15], [16], [17], [25]. In particular, a system developed in Ref.…”
Section: Sensing Toothbrushingmentioning
confidence: 99%
“…Similarly, Ref. [11] used an embedded accelerometer to evaluate toothbrushing performance, using graphical feedback to motivate better performance. In each of these systems, specialized hardware was required, such as a specialized toothbrush or an accelerometer.…”
Section: Sensing Toothbrushingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have tried to evaluate brushing motion three-dimensionally [5][6][7][8][9]. Tosaka, et al [6] demonstrated characteristics of tooth brushing motion and brushing force using a three-dimensional (3-D) accelerometer and a strain tension gage.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the fields of dentistry, several studies have tried to evaluate brushing techniques in terms of tooth brushing motion three-dimensionally [5][6][7][8]. Inada, et al.…”
Section: Introductionmentioning
confidence: 99%